Impact of the COVID 19 pandemic in the productivity and enrollment in a Postgraduate school from Peru (LACCEI, 2024)
The objective of this research is to determinate how the Covid-19 pandemic and sales adaptation plan, impact in the productivity and enrollment intention in the Postgraduate School UPN – Cajamarca, for this it was proposed an applied, quantitative and correlation scope research having as a study population 285 students and commercial area data in the period between 2018 and 2021, it was used the techniques of survey and documentary analysis, and the data was analyzed using Excel and Stgraphics Centurion. The productivity and enrollment intention were possible to find through a diagnosis between the years 2018 – 2021, it was found that there is not a significative difference between them (p 0.05) using Tukey’s test, having an average annual productivity of 98%. Additionally, based on the survey, 80.85% of the study population believe that the university should continue teaching online postgrad courses and the enrollment intention did not have a significative effect due to the pandemic. In conclusion, the students could follow their studies thanks to the strategies generated by the university, so the student was able to continue his studies feeling satisfied with the academic offer generating a positive tendence towards 2021, achieving similar values to those of pre-pandemic.